The MICA-NKG2D axis in clear cell renal cell carcinoma bolsters MICA as target in immuno-oncology. (31st December 2022) - Secchiari, Florencia; Nuñez, Sol Yanel; Sierra, Jessica Mariel; Ziblat, Andrea; Regge, María Victoria; Raffo Iraolagoitia, Ximena Lucía; Rovegno, Agustín; Ameri, Carlos; Secin, Fernando Pablo; Richards, Nicolás; Ríos Pita, Hernando; Vitagliano, Gonzalo; et al.
ABSTRACT: NKG2D is a major natural killer (NK) cell-activating receptor that recognizes eight ligands (NKG2DLs), including MICA, and whose engagement triggers NK cell effector functions. As NKG2DLs are upregulated on tumor cells but tumors can subvert the NKG2D-NKG2DL axis, NKG2DLs constitute attractive targets for antibody (Ab)-based immuno-oncology therapies. However, such approaches require a deep characterization of NKG2DLs and NKG2D cell surface expression on primary tumor and immune cells. Here, using a bioinformatic analysis, we observed that MICA is overexpressed in renal cell carcinoma (RCC), and we also detected an association between the NKG2D-MICA axis and a diminished overall survival of RCC patients. Also, by flow cytometry (FC), we observed that MICA was the only NKG2DL over-expressed on clear cell renal cell carcinoma (ccRCC) tumor cells, including cancer stem cells (CSC) that also coexpressed NKG2D. Moreover, tumor-infiltrating leukocytes (TIL), but not peripheral blood lymphoid cells (PBL) from ccRCC patients, over-expressed MICA, ULBP3 and ULBP4. In addition, NKG2D was downregulated on peripheral blood NK cells (PBNK) from ccRCC patients but upregulated on tumor-infiltrating NK cells (TINK). These TINK exhibited impaired degranulation that negatively correlated with NKG2D expression, diminished IFN-γ production, upregulation of TIM-3, and an impaired glucose intake upon stimulation with cytokines, indicating that they are dysfunctional, display features of exhaustion and an altered metabolic fitness. We conclude that ccRCC patients exhibit a distorted MICA-NKG2D axis, and MICA emerges as the forefront NKG2DL for the development of targeted therapies in ccRCC.